Ecotécnicas aplicáveis à construção civil - Carneiro, Helio Henrique Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The present work approach the main ecotechnics present in nowadays construction. Through this presentation, this work shows the alternative constructions in front of traditional methods looking towards a better usage of natural resources and lower energy expenditure. The ecotechnics studied here were ecological brick, photovoltaic panel, rock wool wall, rainwater and gray water reuse, LED lamps, waste management in civil construction, natural ventilation and green roof. To compile the results, we present two studies cases, one involving green roof and the other involving LED lamps, were used to demonstrate the feasibility and advantages of using sustainable techniques. This study was carried out with the purpose of demonstrating that it is the role of the civil engineer to research and implement technical alternatives that lessen the environment, producing a lesser ecological footprint

Este trabalho tem como abordagem as principais ecotécnicas presentes na construção civil. O estudo em questão, mostra alternativas de construções frente aos métodos tradicionais, visando um melhor aproveitamento dos recursos naturais e, sobretudo, menor gasto energético. As ecotécnicas pesquisadas foram o tijolo ecológico, painel fotovoltaico, parede de lã de rocha, reutilização da água da chuva e águas cinzas, lâmpadas LED, gestão de resíduos na construção civil, ventilação natural e telhado verde. Para a confecção dos resultados, foram utilizados dois estudos de caso, um envolvendo telhado verde e outro envolvendo lâmpadas LED, para demonstrar a viabilidade e vantagens ao se utilizar técnicas sustentáveis. O presente estudo foi realizado com o intuito de demonstrar que é papel do engenheiro civil pesquisar e implantar alternativas técnicas que agridam menos o meio ambiente, produzindo uma pegada ecológica menor
Ecotechniques applicable to civil construction
Keywords: Construção sustentável; Resíduos sólidos; Geração de energia fotovoltaica; Sustainable construction